Dampak Hukum terhadap Penebangan Liar: Studi Kasus UU Lingkungan Hidup di Indonesia - Asri Puannandini, Dewi; Hardianti Putri, Efsa; Gwenda Haryadi, Zaneta (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
llegal logging is a major cause of forest destruction in Indonesia, with widespread impacts on ecosystems, climate change, and the well-being of local communities. To address this issue, the government has issued various regulations, including Law Number 32 of 2009 concerning Environmental Protection and Management (UU PPLH). This article aims to analyze the impact of this law on illegal logging practices and evaluate the effectiveness of its law enforcement through a normative legal approach and empirical case studies in several affected areas. The study shows that although the PPLH Law provides a strong legal basis for prosecuting illegal logging perpetrators, its implementation on the ground still faces many challenges. Factors such as weak oversight, corruption in the forestry sector, limited law enforcement resources, and resistance from illegal logging industry players are significant obstacles. Case studies in Kalimantan and Sumatra show that criminal and administrative sanctions often do not provide an adequate deterrent effect. On the other hand, the success of several regions in reducing illegal logging rates demonstrates that a combination of consistent law enforcement, community participation, and a local wisdom-based approach can increase the effectiveness of environmental policies. This article recommends strengthening institutional capacity, integrating law enforcement across sectors, and regulatory reform to close legal loopholes still exploited by illegal logging perpetrators. In conclusion, environmental law in Indonesia has the potential to curb illegal logging activities, but its effectiveness depends heavily on political commitment, sound governance, and the involvement of all stakeholders.